Postgraduate Medical Residents’ Experience with English Terminology in Regional Anatomy - Munmun, Rydwana; Sultana, Abeda; Yousuf, Syed Abu; Anjum, Nishat; Ritu, Rita Shaha; Islam, Md Shuktarul; Saha, Tripti Moni (Community Based Medical Journal, 2026)
English is the dominant language in medical education and research, but postgraduate residents in non-English-speaking countries often face challenges in mastering technical terminology, particularly in Regional Anatomy. A descriptive, cross-sectional study was conducted in the Department of Anatomy, Bangabandhu Sheikh Mujib Medical University, Dhaka, Bangladesh, between January and December of 2021, to explore postgraduate medical residents’ experiences with English terminology in Regional Anatomy within the Bangladeshi medical education system. Data was collected from postgraduate residents through a structured English language test and questionnaire. Most participants (98.3%) studied in Bangla-medium schools, and only 1.7% had prior English-medium education. Two-thirds (76.3%) agreed that English proficiency is essential for success in Anatomy, yet only 51.7% supported English as the sole medium of instruction. Reading was the top priority skill (78.3%), with textbooks (81.7%) as the preferred material. Histology was the most difficult subdivision due to English (45%), while Embryology was more difficult for undergraduates (32.2%). Reading difficulties were reported by 46.7%, and summarizing difficulties by 40%. Vocabulary was the most challenging aspect (35%), and residents mainly relied on teachers (65%) and online sources (46.3%) for support. Self-assessment showed reading as the strongest skill (mean 3.7±0.6), while speaking was weakest (mean 3.0±0.5). Most of them (82.4%) strongly supported English-in-Anatomy guidelines, prioritizing speaking (46.7%) and academic vocabulary (53.3%). Postgraduate residents face persistent challenges with English in Regional Anatomy, particularly in vocabulary and speaking, highlighting the need for targeted language support and discipline-specific guidelines. CBMJ 2026 January: vol. 15 no. 01 P:240-248